REPOSITORI DATA NASIONAL: TANTANGAN BARU PENGEMBANGAN KOLEKSI PERPUSTAKAAN - Titiek Kismiyati (Media Pustakawan, 2020)
Data has become one of the important things in research. Data as a library collection will make the library more complete. That is why more and more institutions want research results not only in the form of research reports, but also in the form of usable datasets. Data that is managed by the library can be reused by other researchers to allow for further research.The various data that have been collected and processed will become a form of "collection" of the library and can be easily accessed by the users. Therefore, data as part of the library collection will be a challenge in collection development. The National Data Repository is a repository capable of managing various kinds of data, both hard data in the form of numbers or numeric, as well as soft data in the form of textual, audio, and visual. As a library that has both reference and research functions, the National Library of Indonesia is expected to build a national data repository as a reference for researchers in Indonesia.